α-Synuclein and Noradrenergic Modulation of Immune Cells in Parkinson’s Disease Pathogenesis - Butkovich, Laura M.; Houser, Madelyn C.; Tansey, Malú G. (Frontiers in Neuroscience, 2018)
a-synuclein (asyn) pathology and loss of noradrenergic neurons in the locus coeruleus (LC) are among the most ubiquitous features of Parkinson’s disease (PD). While noradrenergic dysfunction is associated with non-motor symptoms of PD, preclinical research suggests that the loss of LC norepinephrine (NE), and subsequently its immune modulatory and neuroprotective actions, may exacerbate or even accelerate disease progression. In this review, we discuss the mechanisms by which asyn pathology and loss of central NE may directly impact brain health by interrupting neurotrophic factor signaling, exacerbating neuroinflammation, and altering regulation of innate and adaptive immune cells.